Exclusive breastfeeding and growth in Croatian infants : comparison to the WHO child growth standards and to the NCHS growth references - Haničar, Branka (Array, 2009)
Abstract: The objective of this study was to compare the growth of exclusively breastfed infants and formula fed infants in eastern Croatia. Additionally, we compared growth patterns and estimated overweight based on the World Health Organization (WHO) child growth standards and the National Center for Health Statistics (NCHS) references. The growth of 88 Croatian infants in two feeding groups (44 breastfed and 44 formula fed) has been researched and presented. The feeding mode was obtained by the 24-hour dietary recall method. Anthropometric measurements were performed at birth and at 1, 2, 3, 4, 6, 9 and 12 months of age. There were significantly lower increases in weight and length in exclusively breastfed infants versus formula fed at 12th month (p<0.05). The weight gain of exclusively breastfed infants was 6651±886g, and among formula fed infants 7247±1254g, and also the exclusively breastfed infants showed significantly lower length gain (25.6±3.1 cm) than formula fed infants (27.3±3.1 cm) in the period from birth to the end of the first year. Differences shown in assessment of growth, depended of growth chart used: WHO child growth standards or NCHS references. A larger number of overweight children were found in the formula fed group in comparison to both references, suggesting that exclusive breastfeeding prevents this occurrence. We conclude that breastfeeding provided the nutrients necessary for infants to keep with the WHO standards of regular growth in children